Análisis comparativo de los centros de detención en España e Italia 2018-2023: Abordar las deficiencias sistémicas y el cumplimiento de los derechos humanos [version 2; peer review: 1 approved, 2 approved with reservations] - Almudena Juárez Rodriguez; Laura María Zanón Bayón-Torres; Mercedes Fernández (Open Research Europe)
Background This article examines the conditions and management of immigration detention centres in Spain and Italy. Methods The study analyses the reports of the Spanish Ombudsman and the Italian National Guarantor on visits to detention and internment centres for foreigners to identify similarities and differences in the functioning of these centres depending on the country. Using a qualitative content analysis approach with NVivo 14 software, 16 reports (10 Italian and 6 Spanish) published between 2018 and 2023 were analysed. The reports were selected based on comparability, excluding non-relevant or non-equivalent documents in both countries. Results The findings reveal deficiencies in health care, staff training, legal care, hygienic conditions, and transparency in managing removals in both countries. Additionally, there is an abuse of detention as a migration control measure and a de facto use of these centres as first reception centres. A significant difference is the length of detention, which is limited to 60 days in Spain compared to 180 days in Italy. Conclusions This analysis highlights the need for reforms to improve conditions in these centres, ensure respect for fundamental rights, and stop their use as first reception centres.